2018
DOI: 10.1186/s12885-018-4367-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PET and laparoscopy in STagIng advanced gastric cancer: a multicenter prospective study (PLASTIC-study)

Abstract: BackgroundInitial staging of gastric cancer consists of computed tomography (CT) and gastroscopy. In locally advanced (cT3–4) gastric cancer, fluorodeoxyglucose positron emission tomography with CT (FDG-PET/CT or PET) and staging laparoscopy (SL) may have a role in staging, but evidence is scarce. The aim of this study is to evaluate the impact and cost-effectiveness of PET and SL in addition to initial staging in patients with locally advanced gastric cancer.MethodsThis prospective observational cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
2
27
4
Order By: Relevance
“…However, this study is insightful, by showing clearly that there is still a high rate of avoidable surgery after a staging laparoscopy. The current prospective PLASTIC study, that evaluates the impact and cost-effectiveness of PET-CT and staging laparoscopy, may confirm our study results in the near future [6].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, this study is insightful, by showing clearly that there is still a high rate of avoidable surgery after a staging laparoscopy. The current prospective PLASTIC study, that evaluates the impact and cost-effectiveness of PET-CT and staging laparoscopy, may confirm our study results in the near future [6].…”
Section: Discussionsupporting
confidence: 78%
“…However, studies have indicated that the sensitivity of CT to detect M1 disease or T4b ranges between 22-33% and 5e69%, respectively [8e11]. Hence, patients with advanced gastric cancer have a high chance of unexpected intraoperative distant metastases or local non-resectability, detected at onset of gastrectomy with curative intent [6].…”
Section: Introductionmentioning
confidence: 99%
“…15 Interventions to promote the implementation of research findings include educational outreach visits. 16 As part of the PLASTIC study, 17 a prospective observational cohort study in The Netherlands that evaluated the impact and cost effectiveness of FDG-PET/CT and SL in addition to initial staging (CT and gastroscopy) in patients with locally advanced gastric cancer, these educational visits started in August 2017. Other factors that have been reported to contribute to slow implementation are the qualities of the guidelines (such as compatibility with existing beliefs and values, or complexity), characteristics of the health care practice setting (including legal and financial aspects), and characteristics of the healthcare professional (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…6,23 For these reasons, the results of the PLASTIC trial, also evaluating histopathology data, are awaited. 17…”
Section: Discussionmentioning
confidence: 99%
“…The most useful techniques are endoscopic ultrasound, computed tomography (CT), magnetic resonance imaging (MRI) and 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET)/CT. At this regard, the PLASTIC trial [5] is an ongoing study that will evaluate the impact and cost-effectiveness of PET and staging laparoscopy in addition to initial staging in patients with locally advanced GC.…”
Section: Introductionmentioning
confidence: 99%